CONCEPT OF SIMPLE LIFE BY H. D.THOREAU - Ihoshev, Kyrylo (Літературний процес: методологія, імена, тенденції, 2019)
In this study, the author examines the concept of “simple life” in the work “Walden; or Life in the Woods” by H. D. Thoreau in the context of transcendental philosophy. The article gives a brief overview of R. Emerson’s works on transcendentalism (which were the foundations of Thoreau’s own philosophical and aesthetic views) and the work of S. Alexander on the philosophy of “simple life” by H. Thoreau. It is determined that one of the main concepts of transcendentalism is “self-reliance”. As a result of the study, it was determined that H. Thoreau’s “simple life” is a practical realization of the “self-reliance” concept and is based on the principles of the “economics of sufficiency”. These are the following principles: self-sufficiency, self-discipline (limiting our own material needs) and the abstinence from excessive (surplus) labor. According to H. Thoreau, people work overmuch because they do not recognize the true value of things. Their toil is unending as they strive for ever greater luxuries which they do not need. Thoreau thought that his fellow-citizen accept the consumerist style of life not because they like it, but because they think that they don’t have a choice. In his book “Walden; Or Life in the Woods” he tried to show them that the other way (in fact, as many ways as they would like) exists and it is possible for anyone to pursue it with success. DOI: https://doi.org/10.28925/2412-2475.2019.1318